Clinical implication of immune checkpoint inhibitor on the chronic hepatitis B virus infection. Issue 9 (15th June 2022) - Hagiwara, Satoru; Nishida, Naoshi; Ida, Hiroshi; Ueshima, Kazuomi; Minami, Yasunori; Takita, Masahiro; Aoki, Tomoko; Morita, Masahiro; Chishina, Hirokazu; Komeda, Yoriaki; Yoshida, Akihiro; Hayashi, Hidetoshi; et al.
Abstract: Aim: The risk of hepatitis B virus (HBV) reactivation with immune checkpoint inhibitors (ICIs) is an important issue that has not yet been fully investigated. ICI is also expected to have an antiviral effect on HBV due to its immune tolerance inhibitory effect. We herein investigated the risk of HBV reactivation and the antiviral effect of ICI administration. Methods: This study included 892 patients on ICIs between September 2014 and May 2021 at our hospital. The frequency of HBV reactivation and antiviral effects were investigated. Results: Among the 892 patients who underwent ICI, 27 were hepatitis B surface antigen (HBsAg) positive. HBV reactivation was evaluated in 24 cases, among which 4.1% (1/24) had HBV reactivation. Nucleic acid analog prophylaxis was not administered to patients with reactivation. In a study of 15 cases, the amount of HBsAg decreased from baseline; 2.18 ± 0.77 log to 48 weeks later; 1.61 ± 1.38 log ( p  = 0.17). Forty‐eight weeks after the start of ICI, disappearance of HBsAg was observed in two out of 15 cases (13.3%), and one case each with and without nucleic acid analog. Conclusion: In rare cases, HBsAg‐positive patients may be reactivated by ICI administration. On the other hand, when ICI is administered, it is expected to have an antiviral effect on HBV due to its immune tolerance inhibitory effect, and future drug development is expected.